Higher Education for Good Teaching and Learning Futures - Czerniewicz, Laura; Cronin, Catherine (Open Book Publishers, 2023)
After decades of turbulence and acute crises in recent years, how can we build a better future for Higher Education? Thoughtfully edited by Laura Czerniewicz and Catherine Cronin, this rich and diverse collection by academics and professionals from across 17 countries and many disciplines offers a variety of answers to this question. It addresses the need to set new values for universities, trapped today in narratives dominated by financial incentives and performance indicators, and examines those "wicked" problems which need multiple solutions, resolutions, experiments, and imaginaries. This mix of new and well-established voices provides hopeful new ways of thinking about Higher Education across a range of contexts, and how to concretise initiatives to deal with local and global challenges. In an unusual and refreshing way, the contributors provide insights about resilience tactics and collective actions across different levels of higher education using an array of styles and formats including essays, poetry, and speculative fiction. With its interdisciplinary appeal, this book presents itself as a provocative and inspiring resource for universities, students, and scholars. Higher Education for Good courageously offers critique, hope, and purpose for the practice and the trajectory of Higher Education.